2021
DOI: 10.1111/1750-3841.15932
|View full text |Cite
|
Sign up to set email alerts
|

The effect of fat and coffee concentration on the consumer acceptance of iced‐coffee beverages

Abstract: The fat content of a product has the potential to influence consumer liking via mouthfeel, taste, and aroma modification. This study aims to determine the effects of fat and coffee concentration on sensory attributes and consumer liking of iced‐coffee beverages. Nine iced‐coffee beverages were formulated: low fat–low coffee; medium fat–low coffee; high fat–low coffee; low fat–medium coffee; medium fat–medium coffee; high fat–medium coffee; low fat–high coffee; medium fat–high coffee; and high fat–high coffee. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The coffee with the milk addition was associated with the sweet attribute (Figure 1A) and had the highest overall liking scores (Table 3). Sweetness increases consumers' liking of many food products [48,49], including coffee and coffee-flavoured dairy beverages [10,50,51]. All the sensory properties that detracted from consumer liking were associated with the PBAs (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The coffee with the milk addition was associated with the sweet attribute (Figure 1A) and had the highest overall liking scores (Table 3). Sweetness increases consumers' liking of many food products [48,49], including coffee and coffee-flavoured dairy beverages [10,50,51]. All the sensory properties that detracted from consumer liking were associated with the PBAs (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…The factorial design feature of the experiment was used to estimate the two-way interaction effects of fat and coffee concentration on overall aroma-liking through linear mixed models. Margins and box plot were extracted to visualize the effects of fat and coffee interaction on aroma-liking (Mahmud et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al showed that liking of coffee-flavored dairy beverages increased with the increase of coffee-flavor intensity to a certain point, but further addition led to decreased liking (Li et al, 2014). Fat has a positive influence on food liking via changing mouthfeel and aroma release (Mahmud et al, 2021). The fat level in milk and lipophilicity (e.g., hydrophobicity) of aromaactive compounds affect aroma release (Frank et al, 2012;Plug & Haring, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Around two billion cups of coffee are consumed every day around the world ( 9 ). Although coffee is traditionally a hot beverage, the popularity and place of cold coffee in the global market have increased considerably with the increasing popularity of coffee varieties and coffee culture ( 10 ). Although the color changes in the materials can be perceived visually, using various color measurement devices is recommended for an objective evaluation.…”
Section: Introductionmentioning
confidence: 99%